PERBEDAAN KEMAMPUAN LITERASI NUMERASI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN PROJECT BASED LEARNING (PjBL) PADA POKOK BAHASAN PROGRAM LINEAR - Khairi Siregar, Alfi; Maysarah, Siti (Euclid, 2024)
This research aims to see the differences in the numeracy literacy abilities of students taught using the Problem Based Learning learning model in class XI MIA 2 and Project Based Learning in class XI MIA 2 in Linear Program material. This research uses an experimental method with a post-test two experimental group design with a population of 5 classes XI MIA totaling 179 students and a sample of 2 classes namely XI MIA 1 totaling 36 students and indicator of numeracy literacy ability. The research results showed that there was no significant difference between classes XI MIA 1 and XI MIA 2 regarding students' numeracy literacy abilities in Linear Program material.